STRATEGI PEMBELAJARAN BERBASIS MULTIMEDIA DALAM MENGAJARKAN GERAKAN SHOLAT PADA ANAK USIA DINI - Sekreningsih Nita; Hermawati Dwi Susari (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Early childhood in millennial times is a native technology that cannot be separated from the use of technology as part of everyday life, including when attending classes. In the implementation of the 2013 curriculum, the ability to conduct worship activities is a basic competence that shows psychomotor development in early childhood. The following research was carried out by implementing a learning strategy with multimedia technology to teach prayer movements to early childhood group A in RA Al-Hadiid Madiun City, with the aim of knowing: 1) Planning learning strategies with multimedia technology in the teaching of prayer movements in early childhood, 2 ) Implementation of learning strategies with multimedia technology in learning early childhood prayer movements, 3) Improving the ability of early childhood prayermovements with learning strategies with multimedia technology. This study uses qualitative and quantitative methods. Data was collected through FGDs and observations to early childhood to find out the main problems, namely the number of children who have difficulty understanding the order of the prayer movements, and in memorizing the recitation of prayers. Data analysis used descriptive method with 5W-1H framework. The results of the study show that the use of prayer application applications is effective to improve the competence of early childhood although not yet optimal. This is because training and habituation are needed to be skilled in the operation of computerbasedlearning media.Keywords:computer-based learning media,  prayer movements, early childhood